Transisi dari PSAK 109 ke PSAK 409: Implikasi Standar Akuntansi Syariah terhadap Transparansi Pengelolaan Zakat - Andi Iswandi (Al-Tasyree: Jurnal Bisnis, Keuangan dan Ekonomi Syariah, 2024)
This study examines the transition from the Indonesian Financial Accounting Standard (PSAK) 109 to PSAK 409 in the context of zakat management in Indonesia. The change in standards reflects the Sharia Accounting Standards Board's (DSAS) efforts to enhance the relevance, reliability, and transparency of financial reporting by zakat management institutions. PSAK 409 introduces a more comprehensive approach to the recognition, measurement, presentation, and disclosure of zakat funds, emphasizing accountability and compliance with Sharia principles. This research adopts a qualitative approach through literature review and in-depth interviews with zakat managers and Islamic accounting practitioners. The findings indicate that the implementation of PSAK 409 has the potential to improve transparency and public trust in zakat institutions, although it faces challenges such as technical readiness, understanding of the new standards, and the need for training among stakeholders. Furthermore, PSAK 409 is seen as aligning zakat reporting with principles of good governance and Sharia integrity, thus supporting the strengthening of the Islamic economic system in Indonesia. The study recommends intensified socialization and training on PSAK 409, as well as collaboration among regulators, academics, and zakat institutions to ensure an effective and sustainable transition.